2022
DOI: 10.1007/s40123-022-00476-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Atropine 0.01% on the Structure and Vasculature of the Choroid and Retina in Myopic Chinese Children

Abstract: Introduction: To explore the short-term effects of atropine 0.01% on the structure and vasculature of the choroid and retina in myopic Chinese children. Methods: This study was a single-center randomized clinical trial. A total of 40 subjects with myopia \ -6.0 D were enrolled and randomized to receive atropine 0.01% once nightly with regular single-vision lenses or to simply wear regular single-vision lenses at an allocation ratio of 1:1. Follow-up visits were planned at 1 month and 3 months. Choroidal thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Wang et al, studied the short-term effect of LDA and reported that 0.01% LDA showed an approximate increase of 20 μm in choroidal thickness among Chinese myopic children. 12 These researchers also reported that none of the other retinal structures were affected by LDA 0.01% treatment. 12 Hence, it is important to identify a potential biomarker to differentiate between responders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wang et al, studied the short-term effect of LDA and reported that 0.01% LDA showed an approximate increase of 20 μm in choroidal thickness among Chinese myopic children. 12 These researchers also reported that none of the other retinal structures were affected by LDA 0.01% treatment. 12 Hence, it is important to identify a potential biomarker to differentiate between responders.…”
Section: Discussionmentioning
confidence: 96%
“…12 These researchers also reported that none of the other retinal structures were affected by LDA 0.01% treatment. 12 Hence, it is important to identify a potential biomarker to differentiate between responders. It has been proposed that increased SFChT can be used as a biomarker in assessing LDA outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Choroid is involved in myopia development because its thickness determines the position of the retina and it produces factors for eye growth and sclera remodeling [37]. Atropine administration at low concentrations (between 0.01 % and 0.05 %) increased choroid thickness in children [38,39] and adults [40], contributing to the recovery of the myopic defect.…”
Section: Exploitation Of Plant Alkaloids In Ophthalmologymentioning
confidence: 99%
“…Jiang [42] second Meta-analysis [45][46][47][48][49][50][51][52][53][54][55] . The demographic and clinical characteristics of the included articles are summarized in Table 3.…”
Section: Choroidal Thickness At Other Positions In Myopic Eyesmentioning
confidence: 99%
“…The quality of the included cohort studies was generally high according to NOS. Effect of atropine on the thickness of the choroidal in children with myopia This Meta-analysis was performed for 6 of 11 eligible studies including 379 myopic children [48][49][50][51][53][54] . There were 281 participants who received 0.01% atropine as myopia control intervention and 98 participants in 1 study received 1% atropine for myopia control.…”
Section: Choroidal Thickness At Other Positions In Myopic Eyesmentioning
confidence: 99%